OUT DOOR AS LEARNING LEARNING CHARACTER CHILDREN EARLY CHILDREN AGE (Study Case in KB Nur Hidayah District of Kuningan) - nunung nuryati (Empowerment : Jurnal Ilmiah Program Studi Pendidikan Luar Sekolah, 2018)
Early childhood is a golden age called golden age. At this time the growth and development of children is very rapid and closely interconnected with each other such as physical growth, motor, emotional social, cognitive, language, and art. Character of children's independence has been achieved at this time one of them through learning outside the classroom or outdoor. The goal to be achieved through this research is to know and describe: 1). to know the objective condition of independence character before applying the learning of outdoor activities in Nur Hidayah Playing Group of Kuningan Regency. 2). know how to apply the learning of outdoor activities in improving the character of independence in the Playing Group Nur Hidayah District Kuningan. 3). knowing the result of independence character after applying outdoor learning activity in Nur Hidayah Playing Group of Kuningan Regency. This study uses qualitative research deskritif Source of this data is students in the Playing Group Nur Hidayah District Kuningan academic year 2017/2018, while the sample of the study amounted to 4 students into the case. The result of the research shows that: 1) the initial condition of the independence character of the child by the teacher is still relatively monotonous and conventional in that it is associated with the work which is limited to the learning that is related to the outdoor activities 2) the application of outdoor learning is done through the simple learning stages not complicated and can be followed by the child. 3). The results of the application of learning through outdoor activities in certain forms have contributed as in improving the character of independence of children in general, especially when starting to work with friends and the division of tasks with other friends meningkast significantly. Based on the results of the discussion that has been described learning activities with outdoor activities very positive impact on improving the character of independence of children in the Playing Group Nur Hidayah District Kuningan academic year 2017/2018. The result of obsevation of increasing the independence character of the children from before and after doing the application of outdoor activities showed the optimal and significant development.Early childhood is a golden age called golden age. At this time the growth and development of children is very rapid and closely interconnected with each other such as physical growth, motor, emotional social, cognitive, language, and art. Character of children's independence has been achieved at this time one of them through learning outside the classroom or outdoor. The goal to be achieved through this research is to know and describe: 1). to know the objective condition of independence character before applying the learning of outdoor activities in Nur Hidayah Playing Group of Kuningan Regency. 2). know how to apply the learning of outdoor activities in improving the character of independence in the Playing Group Nur Hidayah District Kuningan. 3). knowing the result of independence character after applying outdoor learning activity in Nur Hidayah Playing Group of Kuningan Regency. This study uses qualitative research deskritif Source of this data is students in the Playing Group Nur Hidayah District Kuningan academic year 2017/2018, while the sample of the study amounted to 4 students into the case. The result of the research shows that: 1) the initial condition of the independence character of the child by the teacher is still relatively monotonous and conventional in that it is associated with the work which is limited to the learning that is related to the outdoor activities 2) the application of outdoor learning is done through the simple learning stages not complicated and can be followed by the child. 3). The results of the application of learning through outdoor activities in certain forms have contributed as in improving the character of independence of children in general, especially when starting to work with friends and the division of tasks with other friends meningkast significantly. Based on the results of the discussion that has been described learning activities with outdoor activities very positive impact on improving the character of independence of children in the Playing Group Nur Hidayah District Kuningan academic year 2017/2018. The result of obsevation of increasing the independence character of the children from before and after doing the application of outdoor activities showed the optimal and significant development.